1992
DOI: 10.1111/j.1600-0447.1992.tb03240.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood serotonin, serum melatonin and light therapy in healthy subjects and in patients with nonseasonal depression

Abstract: The 24-h rhythms of blood serotonin and serum melatonin were determined in 39 unmediated inpatients with nonseasonal affective disorder and in 14 healthy men and women after 7 days of morning bright-light (2500 lx) or dim-light (50 lx) treatment. Bright-light treatment led to a more than 50% decrease in the Hamilton Rating Scale for Depression (HRSD) score in 4/19 patients and dim light in 1/17 patients. After light treatment the mesor (the daily mean estimated by cosinor analysis) of patients' and subjects' m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
2
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 24 publications
2
26
2
2
Order By: Relevance
“…This small group size raises the possibility of insufficient power to detect differences. The strong point of the present study is that it is a within-subjects comparison, in contrast to the between-subjects comparison of two other studies that examined clinical change in relation to chronobiological variables (Rao et al, 1992;Yamada et al, 1995). In this context, the present study might play a role in the discussion on the possible pathogenetic role of circadian phase disturbances in depression.…”
Section: Limitations Of the Studycontrasting
confidence: 41%
See 3 more Smart Citations
“…This small group size raises the possibility of insufficient power to detect differences. The strong point of the present study is that it is a within-subjects comparison, in contrast to the between-subjects comparison of two other studies that examined clinical change in relation to chronobiological variables (Rao et al, 1992;Yamada et al, 1995). In this context, the present study might play a role in the discussion on the possible pathogenetic role of circadian phase disturbances in depression.…”
Section: Limitations Of the Studycontrasting
confidence: 41%
“…The result that opposite phase shifts within the same subject do not result in opposite mood changes strengthens the conclusion that no clear relationship between shifts of the circadian system and mood exists in the present group of depressives and healthy subjects. This is the third study that concludes that the possible effects of light in nonseasonal depressives are not mediated by chronobiological mechanisms (Rao et al, 1992;Yamada et al 1995). Alternative explanations for the lack of a mood change in the present study are that the phase shifts induced were too small to obtain effects or that the duration of the shifts did not last long enough.…”
contrasting
confidence: 43%
See 2 more Smart Citations
“…The comprehensive analysis also suggests that light therapy can improve melatonin amplitude and cyclical sleep patterns along with improvement in depression score [29]. There are currently no guidelines to determine which patients will benefit from light therapy, as a few studies have demonstrated no impact of light therapy on patients with NSAD [20,21,[30][31][32]. Furthermore, there has been no systematic evaluation and synthesis of the published literature regarding characteristics (colour, intensity), exposure dose (duration and timing) and the mode of delivery (light boxes, visor etc) of light for use as a treatment for NSAD patients.…”
Section: Introductionmentioning
confidence: 99%